Pengaruh Keputusan Investasi, Kondisi Makro Ekonomi dan Risiko Perusahaan pada Return Saham Studi pada Industri Manufaktur PT. Bursa Efek Indonesia - Haruman, Tendi (Business and Management Review, 2010)
Economic development of Indonesia has increased risk of global financial crisis. The global crisis has affected the economy of the world, including Indonesia. The impact is increasingly felt both through the market for goods and financial markets (banking and capital markets). Changes and developments in various economic variables of a country would give effect to the capital market in Indonesia. The objective of this research is to investigate the effect of investment factors, inflation factors, international monetary factors and risk to price return of Manufacturer Industries in 2000 – 2007. This research used four regression model, and the models are: 1st model to investigate effect of the investment factors (Debt to Equity Ratio, Dividend Payout Ratio, Profitability, and Growth) to the investment decisions; 2nd model used to investigate effect of the inflation factors (SBI, foreign exchange, and M2) to the inflation; 3rd model used to investigate effect of the investment,, inflation, the fed, dow jones index, oil price and firm risk to the price return. Population of this research is manufacturing companies listed in BEI. The sampling method used in this research is purposive sampling and the results are 128 companies according to the criteria of the sample. Pooling data method and judgment sampling is used to collect the data and two stage least squares (2 SLS) as the analysis method. Base on the hypothesis test it can be summarized that all predictor have significant effect simultaneously. Result of the 1st Model, Dividend Payout Ratio, Profitability and Growth Effect to the Investment partially ; 2nd model,  SBI, KURS, and M2 effect to the inflation partially; 3rd model investment, inflation, the fed, and oil price effected to the price return partially. Keywords:   price return, price book value, investment, inflation, the fed, dow jones index, firm risk, two stage least square, pooled data.